PROBLEMS AND PROSPECTS OF DEVELOPMENT OF THE MARKET OF FINANCIAL SERVICES IN UKRAINE - Урусова, З. П.; Ярмош, В. В.; Урусов, А. А. (Scientific Progress & Innovations, 2014)
Financial service market is a market in which to exchange financial resources, the provision of credit and capital mobilization. The objective basis for the functioning of the financial market is different needs in financial resources, availability of sources of meeting this need. Market of financial services is one of the mechanisms for ensuring competitiveness of the economy, as the allocation of financial resources in this market takes place on a competitive basis, which allows direct investment flows in the most attractive segments of the economy and thus contribute to economic growth. That is why there are considered and identified factors that are crucial for increasing Ukraine's competitiveness in the market of financial services on a global and regional scale.